OPTIMASI FASE GERAK PADA KLT DAN IDENTIFIKASI METABOLIT SEKUNDER Ipomoea pes-caprae - Lalu Husnul Hidayat; Yosi Bayu Murti; Nunung Yuniarti; Akhmad Riski (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Ipomoea pes-caprae (L.) R.Br traditionally used to treat pain, skin infections, inflammation, and rheumatic disorders. In vitro studies also reported antioxidant, anti-inflammatory, and antimicrobial potential activities obtained from secondary metabolites such as flavonoids, tannins, terpenoids, steroids, saponins, and alkaloids contained in Ipomoea pes-caprae. The purpose of this study is to optimize the mobile phase and identify secondary metabolite compounds of Ipomoea pes-caprae. The analysis used thin layer chromatography (TLC) in identifying compounds responsible for providing antioxidant activity with a spray reagent in the form of DPPH. The results showed the ideal of mobile phase, namely Chloroform: Ethyl Acetate: Methanol: Formic Acid (2: 7: 0.5: 0.5). Ethanol extract of 96% leaves has antioxidant activity with a DPPH spray reaction than ethyl acetate and N-hexane extracts. The metabolite profiles in samples with various specific reagents include the group of polyphenols, alkaloids and flavonoid compounds. Based on the results of the descriptive analysis, it was shown that the most dominant group of flavonoid compounds from ethanol extract was 96% of Ipomoea pes-caprae leaves, so it had a strong correlation with antioxidant activity.